2019
DOI: 10.1590/s2175-97902019000117870
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization and in vivo performance of mefenamic acid-sodium diethyldithiocarbamate based liposomes

Abstract: Mefenamic acid (MFA) is a hydrophobic drug with low dissolution rate. This study aimed to develop stable and reproducible aqueous formulations of MFA using liposomes as drug carriers. The drug entrapment, particles size and drug release profiles, and stability and reproducibility of the liposomes were determined. In addition, the maximum tolerated dose (MTD) was determined in rats via the oral and intraperitoneal routes of administration. Also, the anti-inflammatory efficacy of these liposomes was evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is used for treatment of muscular aches, menstrual cramps, headache, dental pain, and as a painkiller after surgeries. 1 − 3 Based on its structure, mefenamic acid is a derivative of N -aryl anthranilic acid and it belongs to the class of fenamic acids. 4 6 Like many NSAIDs, mefenamic acid binds to cyclooxygenase (COX) and thus inhibits the synthesis of prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used for treatment of muscular aches, menstrual cramps, headache, dental pain, and as a painkiller after surgeries. 1 − 3 Based on its structure, mefenamic acid is a derivative of N -aryl anthranilic acid and it belongs to the class of fenamic acids. 4 6 Like many NSAIDs, mefenamic acid binds to cyclooxygenase (COX) and thus inhibits the synthesis of prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
“…Mefenamic acid ( 1 , Scheme ) is a nonsteroidal anti-inflammatory drug (NSAID) with a wide range of pharmacological activities such as analgesic, anti-inflammatory, and antipyretic activity. It is used for treatment of muscular aches, menstrual cramps, headache, dental pain, and as a painkiller after surgeries. Based on its structure, mefenamic acid is a derivative of N -aryl anthranilic acid and it belongs to the class of fenamic acids. Like many NSAIDs, mefenamic acid binds to cyclooxygenase (COX) and thus inhibits the synthesis of prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the liposomal drug delivery system can enhance the therapeutic efficacy and reduce drug toxicities, which were attributed to their ability to enhance the bioavailability of poorly water-soluble drugs [ 14 , 15 , 16 , 17 , 18 ]. Liposomes can improve the bioavailability of drugs generally by enhancing their absorption, protecting the drugs from rapid metabolism, and prolonging biological half-life [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that the liposomal drug delivery system can enhance the therapeutic efficacy and reduce drug toxicities, which were attributed to their ability to enhance the bioavailability of poorly water-soluble drugs [14][15][16][17][18]. Liposomes can improve the bioavailability of Several studies have demonstrated that the liposomal drug delivery system can enhance the therapeutic efficacy and reduce drug toxicities, which were attributed to their ability to enhance the bioavailability of poorly water-soluble drugs [14][15][16][17][18]. Liposomes can improve the bioavailability of drugs generally by enhancing their absorption, protecting the drugs from rapid metabolism, and prolonging biological half-life [19].…”
Section: Pharmacokinetic Studymentioning
confidence: 99%